PENGARUH KINERJA DAN MOTIVASI KARYAWAN TERHADAP HASIL PRODUKSI PANEN BUAH KELAPA SAWIT DI PT. PERKEBUNAN NUSANTARA VI KABUPATEN TEBO PROVINSI JAMBI - Lubis, Silvia Zarmila; Susanto , Andi Heru (Lembaga Pengembangan Kinerja Dosen, 2023)
Increasing the company's productivity numbers can be caused by the performance of its employee members where the bad work they get will affect the level of the company. Performance is a job that is carried out and carried out in accordance with the regulations given by the company. Besides that, motivation is also an aid to motivate employees to increase work productivity and also income for the company. This study aims to determine whether there is a positive influence of performance on production results, motivation on results. This study used an associative quantitative approach with a sample of 100 respondents. The instrument used is a questionnaire. Instrument quality testing includes validity and reliability tests. Data analysis used descriptive analysis, while for testing the hypothesis using multiple linear regression analysis, the coefficient of determination, the classical assumption test, and the partial test (T test). The results of the study show that there is a significant relationship between performance, employee motivation and production results.